Heart rate variability is correlated with perceived physical fitness in elite soccer players - Ravé, G.; Zouhal, H.; Boullosa, D.; Doyle-Baker, P. K.; Saeidi, A.; Ben Abderrahman, A.; Fortrat, J.-O. (Journal of Human Kinetics, 2020)
Heart Rate Variability (HRV) has been typically used to monitor athletes` physical fitness readiness. The supine position maximizes parasympathetic tone, which is important for monitoring in continuous aerobic sports, however, this is not the case of team sports that rely on anaerobic intermittent bouts, thus increasing sympathetic activation and vagal withdrawal. We hypothesized that HRV during sympathetic activation and vagal withdrawal would be a useful marker to evaluate perceived physical fitness in team sports. HRV was measured in both supine and standing positions during the mornings of 4 match days in 14 professional players. The supine Root Mean Square of the Successive Differences (RMSSD), as well as spectral analysis indices were recorded. Perceived physical fitness was assessed after each match by means of a visual analogue scale (VAS). Supine RMSSD was moderately correlated with perceived physical fitness (rho = 0.416), however, larger correlations were observed for supine and standing spectral indices (rho > 0.5). Correlation between RMSSD and Total Power was very large, thus questioning the usual interpretation of RMSSD (rho > 0.7). Standing Spectral HRV analyses may be a useful method for evaluating perceived physical fitness in the context of team sports. RMSSD may reflect the overall variability of HR and not only the parasympathetic influence, as observed in the current study.